2017
DOI: 10.1007/978-3-319-66197-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Information Flow Tracking for Linux Handling Concurrent System Calls and Shared Memory

Abstract: Abstract. Information flow control can be used at the Operating System level to enforce restrictions on the diffusion of security-sensitive data. In Linux, information flow trackers are often implemented as Linux Security Modules. They can fail to monitor some indirect flows when flows occur concurrently and affect the same containers of information. Furthermore, they are not able to monitor the flows due to file mappings in memory and shared memory between processes. We first present two attacks to evade stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…These methods can be applied using commercial off-the-shelf kernel logging frameworks, such as auditd [4] or event tracing windows [3], which allow the logging of system calls. Some works propose the alternative instrumentation of the kernel with an optimized design that includes security considerations [34], [7], [40]; other approaches couple the IFT with tag propagation policies [22] [18]. Tag propagationbased policies can be coupled to access control policies or attack detection policies; these may make it possible to achieve a finer-grained causality tracking.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods can be applied using commercial off-the-shelf kernel logging frameworks, such as auditd [4] or event tracing windows [3], which allow the logging of system calls. Some works propose the alternative instrumentation of the kernel with an optimized design that includes security considerations [34], [7], [40]; other approaches couple the IFT with tag propagation policies [22] [18]. Tag propagationbased policies can be coupled to access control policies or attack detection policies; these may make it possible to achieve a finer-grained causality tracking.…”
Section: State Of the Artmentioning
confidence: 99%
“…1) Information Flow Monitoring inside Kernel Space: Although information flows can be deduced from system call monitoring [17], [31], considerable work has been performed to instrument the Linux kernel by leveraging the Linux Security Module framework and netfilter modules to enable a finergrained observation of information flows produced by system call invocations [39], [42], [40]. In particular, RfBlare [18] proposes a solution to handle information flow monitoring evasions that leverage race conditions among system calls. In [7], the authors propose the insertion of new dedicated hooks to record information flows into the provenance model.…”
Section: A Computing An Approximation Of Causal Dependencies Among Amentioning
confidence: 99%
“…These structures expose attributes of the underlying kernel objects they represent (e.g., inode, process, shared memory), 1 # d e f i n e KERNEL_QUERY 2 # i n c l u d e " i n c l u d e / camquery . h " r e t u r n 0 ; 32 } 33 34 QUERY_NAME ( "My Example Query " ) ; 35 QUERY_DESCRIPTION ( " An example q u e r y " ) ; 36 QUERY_AUTHOR ( " John Doe " ) ; 37 QUERY_VERSION ( " 0 . 1 " ) ; 38 QUERY_LICSENSE ( " GPL " ) ; 39 r e g i s t e r _ q u e r y ( i n i t , i n _ e d g e , o u t _ e d g e ) ;…”
Section: Camquery Apimentioning
confidence: 99%
“…The LSM framework [69] was originally implemented to support Mandatory Access Control (MAC) schemes but not information flow tracking. Recent work by Georget et al [35,36] demonstrated, through static analysis of the kernel code base, that the LSM framework is applicable to information flow tracking, and that by adding a small number of LSM hooks, it was possible to properly intercept all information flows between kernel objects. Building on their work, we maintain a patch [5] to the LSM framework that allows CamFlow, and by extension CamQuery, to provide stronger guarantees than do previous whole-system provenance capture mechanisms.…”
Section: Ensuring Completeness and Accuracymentioning
confidence: 99%
“…Only a limited number of system calls such as read or write have to be modified. To handle tags associated to files, we rely on RFBlare [16]. RFBlare is a modified Linux kernel that implements an OS-level DIFT monitor.…”
Section: Kernel Supportmentioning
confidence: 99%